Spanish educational cooperation abroad (Journal of Parents and Teachers, 2014)
The elimination of the particularisms that distance the European educational systems would contribute to economic development and peace. Moreover, the phenomenon of migration forces receiving countries to provide quality education to newcomers. With regard to the Spanish educational cooperation abroad, Spain needs to promote Spanish and make itself known as a nation of culture by opening centers that promote the teaching of the Spanish language and the Spanish culture. Furthermore, Spain should promote the teaching of Spanish as a foreign language in European educational centers. It is necessary to insist on the role that the educational centers should play as protagonists of a community action.
Keywords: Education; European Union; migration; education centers; Spanish; educational cooperation; Spain